Orgasmic dysfunction among Malay diabetic women in Malaysia - Ismail, Adibah Hanim; Baw, Rawa; Sidi, Hatta; Ng, Chong Guan; Midin, Marhani; Nik Jaafar, Nik Ruzyanei; Das, Srijit; Abdul Manaf, Mohd. Rizal (Elsevier, 2014)
Objectives The present study aimed to determine the prevalence and associated factors of orgasmic dysfunction among Malay women with type 2 diabetes mellitus in Malaysia. Methods This cross-sectional study involved 347 women (174 non diabetic and 173 diabetic subjects) who attended the diabetic clinic in a university hospital. Orgasmic dysfunction was assessed using the orgasmic subscale of Malay Version of the Female Sexual Function Index (MVFSFI). Sociodemographic information of the subjects was collected with a pre-designed questionnaire. Results Prevalence of orgasmic dysfunction among Malay women was 13.3% and 10.3% in type 2 diabetes mellitus and control group, respectively. However, the difference was not statistically significant. Multivariate logistic regression analysis showed that unemployment (Adjusted Odds Ratio, AOR = 2.69, 95% CI = 1.22, 5.97) and lower academic status (AOR = 0.35, 95% CI = 0.17, 0.72) were significantly associated with sexual orgasmic dysfunction in diabetic women. Conclusion Orgasmic dysfunction was highly prevalent among the Malay women regardless of the diabetic state. It is recommended that orgasmic dysfunction in women with diabetes should be assessed during routine clinical health visit to the hospital for early treatment.